Mazindol anorexia is mediated by activation of dopaminergic mechanisms. - Kruk, Z L (1976)
1 Anorexia in rats following injections of mazindol (0.1-8 mg/kg i.p.) could be antagonized by pretreatment with a dopamine receptor blocker (primozide) but not by pretreatment with an alpha-adrenoceptor blocker (phenoxybenzamine), a beta-adrenoceptor blocker ((-)-propranolol), or a 5-hydroxytryptamine receptor blocker (methergoline). 2 In rats with a unilateral lesion in the substantia nigra made by stereotaxic injection of 6-hydroxydopamine, mazindol caused a dose-dependent turning towards the lesioned side, indicating an indirect mechanism of action. This effect could be antagonized by pretreatment with a dopamine receptor blocker. 3 In rats pretreated with reserpine and alpha-methyl-p-tyrosine, mazindol did not have any motor stimulant action. 4 In vitro studies with synaptosomes prepared from rat brain, indicated that mazindol blocks uptake and causes release of dopamine. 5 It is concluded that the anorectic action of mazindol is mediated by a dopaminergic mechanism.